Tinjauan Yuridis Terhadap Putusan Pengadilan Mengenai Tindak Pidana Perdagangan Orang dengan Modus Ekploitasi Seksual di Bantul - Bambang Supriyanta; Sigit Herman Binaji (Universitas Janabadra, 2019)
Human trafficking is recruitment, delivery, removal, gathering or admitting people by threatening,kidnaping,deceiving or using violence or other forms of forcement, kidnaping, deceiving, lying or or abusing of power risky position or taking and giving payment or getting advabtages in order to get agreement from the authority of other persons for exploitation. And the action of human trafficing is an action or a series of actions which fulfil the aspects of crime in the the rules of law.The most prominent of human trafficking is the sexual exploitation. This situation is so terrifying in the Bantul region. The victims of human trafficking are women and children, at least, two cases have been brought to court in the State Court of Bantul in the period of 2016 to 2017. They are the case of No.147 Pid.Sus 2016 PN.Btl and the case of No.148 Pid.Sus 2016 PN.Btl. Based on the facts, the questions arise are how the juridical implementation to the human trafficking through sexual exploitation in Bantul regency is and what makes the cases of human trafficking through sexual exploitation in Bantul regency arise.The objectives of this research are 1. To give explanation of juridical study of adjudication to the human trafficking through sexual exploitation in Bantul regency, 2. To give explanation why the crime of human trafficking arise through sexual exploitation in Bantul regency.The result of this research is study of adjudication of the human trafficking through sexual exploitation in Bantul regency. It includes, judges must consider the system of crime act provement. b judges must consider the principle of legality of the law. And the reasons of the human trafficking through sexual exploitation in Bantul regency are the factors of economic religion family education and facilities in Bantul regency.